Coherent Ag-rich nanoprecipitates/β-Ag2Se flexible film with unprecedented thermoelectric performance by liquid-like sintering - Jie Gao; Jiahui Li; Lei Miao; Lida Jia; Pengfei Qiu; Tingwei Yin; Sijing Zhu; Xinyu Yang; Jia-Chen Guo; Jun-Liang Chen; Xiaoyang Wang; Eiji Nishibori; et al. (Nature Communications)
Abstract β-Ag2Se holds a great promise for wearable thermoelectric generators due to its good mechanical properties and biocompatibility. However, optimizing its power factor through alterations in the Ag/Se stoichiometric ratio or incorporating secondary phases has reached the limitation. This work adopts a liquid-like sintering strategy, namely employing the migration and precipitation of silver ions from metallic silver to the silver selenide during the spark plasma sintering process to construct significantly sized and coherent Ag-rich nanoprecipitates within flexible Ag/β-Ag2Se composite films, thereby achieving an unprecedented power factor exceeding 4000 μWm−1K−2 at 303 K. The Ag-rich nanoprecipitates play a crucial role in elevating the carrier concentration, enhancing the density-of-states effective mass, and mitigating carrier scattering caused by phase interfaces and acoustic phonons. The generator containing 5 pieces of optimal films shows an normalized output power density of 10.89 μWcm−1K−2 under a temperature difference of 26.0 K. This study strongly suggests that the creation of Ag-rich nanoprecipitates is an effective avenue for improving the electrical performance of β-Ag2Se-based thermoelectric materials.